The Role of Muscle Stem Cells in Regeneration and Recovery after Denervation: A Review. Issue 3 (March 2019) - Wong, Alvin; Pomerantz, Jason H.
Abstract : Background: Skeletal muscle denervation is a complex clinical problem that still lacks a comprehensive solution. Previous studies have suggested that prolonged periods of denervation lead to a decline in the muscle stem cell population, negatively affecting the ability of muscle to regenerate following reinnervation. Recent advances in the understanding of muscle stem cell biology, along with new techniques that increase the ability to identify and manipulate these cells, provide an opportunity to definitively address the impact of muscle stem cells in recovery from denervation and their potential role in treatment. Methods: A comprehensive review of the literature on the biology of muscle denervation, and the effect of denervation injury on muscle stem cell behavior, was performed. Results: In this review, the authors discuss the current understanding of muscle stem cell biology in the setting of denervation atrophy, review barriers to successful reinnervation, and review options available to patients following denervation injury. The authors also discuss potential use of muscle stem cells in future therapies. Conclusions: Although the clinical treatment of prolonged denervation injury has improved in recent years, regeneration of native muscle remains elusive. Muscle stem cells have been demonstrated to be of central importance in muscle regeneration following injury, and may be a powerful tool that provides effective new options for future treatments. Additional work clarifying the effect of denervation injury on satellite cells is needed to determine whether they are a limiting factor in recovery and to demonstrate whether their clinical use as a cell-based therapy in denervation injury can be efficacious.